Improved Semiautomated 4D Flow MRI Analysis in the Aorta in Patients With Congenital Aortic Valve Anomalies Versus Tricuspid Aortic Valves. Issue 1 (January 2016) - Schnell, Susanne; Entezari, Pegah; Mahadewia, Riti J.; Malaisrie, S. Chris; McCarthy, Patrick M.; Collins, Jeremy D.; Carr, James; Markl, Michael
Abstract : Objective: The aim of this study was to systematically investigate a newly developed semiautomated workflow for the analysis of aortic 4-dimensional flow MRI and its ability to detect hemodynamic differences in patients with congenitally altered aortic valve (bicuspid or quadricuspid valves) compared with tricuspid aortic valves. Methods: Four-dimensional flow MRI data were acquired in 20 patients with aortic dilatation (9 tricuspid aortic valves, 11 congenitally altered aortic valves). A semiautomated workflow was evaluated regarding interobserver variability, accuracy of net flow, regurgitant fraction and peak systolic velocity, and the ability to detect differences between cohorts. Results were compared with manual segmentation of vessel contours. Results: Despite the significantly reduced analysis time, a good interobserver agreement was found for net flow and peak systolic velocity, and a moderate agreement was found for regurgitation. Significant differences in peak velocities in the descending aorta ( P = 0.014) could be detected. Conclusions: Four-dimensional flow MRI-based semiautomated analysis of aortic hemodynamics can be performed with good reproducibility and accuracy. Abstract : Supplemental digital content is available in the text